Multi-photon 4D printing of complex liquid crystalline microstructures by in situ alignment using electric fields - Münchinger, Alexander; Hahn, Vincent; Beutel, Dominik; Woska, Simon; Monti, Joël; Rockstuhl, Carsten; Blasco, Eva; Wegener, Martin (Advanced Materials Technologies, 2022)
An approach is presented to align the direction of liquid crystal networks or elastomers in situ during multi-photon laser printing for each voxel in three dimensions by applying a quasi-static electric field with variable orientation. This approach enables the making of 3D micro-heterostructures operating under ambient conditions that show large-amplitude elastic actuation, with temperature serving as the stimulus (“4D microstructures”). The approach involves two novelties. First, a dedicated sample cell with a variable height suitable for laser printing is introduced. It is based on optically transparent electrodes and allows to apply arbitrary electric field vectors in three dimensions, for example, parallel or normal to the substrate plane. Second, a variable optical phase plate combined with a pivotable half-wave plate warrants a single well-defined laser focus for nearly all possible quasi-static electric field vectors. Without the latter, one generally obtains two spatially separated laser foci, an ordinary and an extraordinary one, due to the optical birefringence of the medium induced by the alignment of the liquid crystal director via the applied quasi-static electric field. The versatility of the approach is illustrated by manufacturing and characterizing several exemplary architectures.